Sarawak Gems: Barry Roper special collections at Sarawak State Library / Sabariah Abd Samad, Imilia Ibrahim and Nordiana Mohd Nordin - Abd Samad, Sabariah; Ibrahim, Imilia; Mohd Nordin, Nordiana (Faculty of Information Management, 2022)
Sarawak is rich with interesting landscapes and various ethnicities among the members of the society. To ensure the arts and cultural heritage, as well as the collection of publications related to the state, are gathered under one roof, the State Library of Sarawak has taken the initiative to collect all the materials and make them available as their Sarawakiana collections. A special collection was selected as a sample for the case study to understand the treatment of Sarawakiana collections. This paper discusses the purpose of acquiring the collections, the treatment, and the relevance of Barry Roper's collections to Sarawak State Library.